Contrôlabilité exacte d’un problème avec conditions de ventcel èvolutives pour le système linéaire de l’élasticité - Heminna, Amar (Revista Matemática Complutense, 2001)
In this work, we examine the exact controllability of the solution of a linear elasticity system, with evolutive Ventcel’s conditions,( see:[3]), in a bounded domain of R3. We use the Hilbert uniqueness methode,(H.U.M), of J.L.LIONS, (see:[9]); some multipliers are defined on the boundary; the curvature tensor (see:[6]), appears when computing some boundary integrals. This work can be inserted in the framework of the study of the exact controllability and stabilisation of various problems with Ventcel’s conditions (see:[3],[4]).